PENGARUH MEKANISME CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN PERUSAHAAN PERBANKAN - Daniel Felimanto Hartono; Yeterina Widi Nugrahanti (Dinamika Akuntansi Keuangan dan Perbankan, 2014)
The purpose of this study is to evaluate the effect of corporate governance mechanism on financial performance in thebanking sector. The independent variables consist of institutional ownership, management ownership, independent boarddirector, board of directors and audit committee. Bank performance is measured by Return On Equity (ROE). Thepopulation in this study is the bank listed in Indonesia Stock Exchange (IDX) in the period 2011-2013. This study datacome from bank annual reports obtained from the Indonesian Stock Exchange website and Indonesian Capital MarketDirectory (ICMD). By purposive sampling method, this research got28 samples in each period, so 84 (28 sample × 3years) annual report will be used in this research. The analysis technique used to test the hypothesis is multiple regressionwith SPSS 16.The results show that the board of directors have a positive effect to the bank performance. Iinstitutionalownership has a negative effect to bank performance. However, management ownership, independent board and auditcommittee have no influence to bank performance.Keywords: Institutional ownership, Management ownership, Independent board directors, Board of directors, Auditcommittee, Return on equity, corporate governance